Cana de açúcar: Indicadores de fertilidade física e vulnerabilidade do solo em Tucumán, Argentina - Tesouro, Mario Omar; Roba, Marcos Andrés; Romito, Angel; Neiman, Otto Erik; Fernandez Ullivarri, Enrique; Donato, Lidia Beatriz (SBEA, 2021)
In a sugarcane experimental site (Famaillá, Tucumán, Argentina) there were determined the load-strain ratio, the pre-compression stresses and the compression indexes of unaltered soil samples. Test procedure was based on the methodology described in ASTM D 2435 03. Soil samples were soaked for 48 hours in order to reach the saturation state before being subjected to vertical pressures from 6 to 1478 kPa. The time of application was the necessary one to allow the drainage of excess water from the soil sample. Deformation of the soil sample was plotted as a function of the logarithm of the time. Voids ratio were established as a function of the logarithm of the pressure and, from this function, the mentioned parameters were calculated. Results obtained from the consolidation tests seem to show the effect of the history of loads exerted on the soil. There is a high gradient of reduction of void ratio, which tends to compromise the future physical integrity of the soil.